Zmym4 is required for early cranial gene expression and craniofacial cartilage formation - Jourdeuil, Karyn; Neilson, Karen M.; Cousin, Helene; Tavares, Andre L. P.; Majumdar, Himani D.; Alfandari, Dominique; Moody, Sally A. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The Six1 transcription factor plays important roles in the development of cranial sensory organs, and point mutations underlie craniofacial birth defects. Because Six1's transcriptional activity can be modulated by interacting proteins, we previously screened for candidate interactors and identified zinc-finger MYM-containing protein 4 (Zmym4) by its inclusion of a few domains with a bona fide cofactor, Sine oculis binding protein (Sobp). Although Zmym4 has been implicated in regulating early brain development and certain cancers, its role in craniofacial development has not previously been described. Methods: We used co-immunoprecipitation and luciferase-reporter assays in cultured cell to test interactions between Zmym4 and Six1. We used knock-down and overexpression of Zmym4 in embryos to test for its effects on early ectodermal gene expression, neural crest migration and craniofacial cartilage formation. Results: We found no evidence that Zmym4 physically or transcriptionally interacts with Six1 in cultured cells. Nonetheless, knockdown of endogenous Zmym4 in embryos resulted in altered early cranial gene expression, including those expressed in the neural border, neural plate, neural crest and preplacodal ectoderm. Experimentally increasing Zmym4 levels had minor effects on neural border or neural plate genes, but altered the expression of neural crest and preplacodal genes. At larval stages, genes expressed in the otic vesicle and branchial arches showed reduced expression in Zmym4 morphants. Although we did not detect defects in neural crest migration into the branchial arches, loss of Zmym4 resulted in aberrant morphology of several craniofacial cartilages. Discussion: Although Zmym4 does not appear to function as a Six1 transcriptional cofactor, it plays an important role in regulating the expression of embryonic cranial genes in tissues critical for normal craniofacial development.